The Influence of Android-Based Digital Comics on the Social Skills to Prevent the Covid-19 Through Student Social Interaction - Muhammad Rais; Hartoto Hartoto; Farida Aryani (Universitas Negeri Makassar, 2022)
This study aims to determine the effect of digital comic media, including self-awareness comics and self-regulation comics, on the social skills of elementary school students. This study used a quantitative approach with an ex post facto design involving 180 students selected through a purposive sampling technique. Data were analyzed using classical assumption testing and multiple linear regression analysis. The study results show that digital comic media based on Android, which contains material on self-awareness and self-regulation, positively and significantly improved students' social skills in the context of self-management about the prevention of Covid-19 in the daily social environment of the school. Self-awareness and self-regulation content as part of social skills presented in an Android-based digital comic version become students' daily reading to implement health protocols at school. Self-awareness and self-regulation comics can raise sensitivity to students’ self-introspection in recognizing feelings converted into positive behaviors and managing themselves in synergy with the learning environment, interacting and making decisions independently to solve their internal problems.